2010
DOI: 10.5539/ijb.v2n1p3
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Prdx1 and Prdx6 in Liver Cells by Serum and TPA

Abstract: Peroxiredoxins are thiol-specific antioxidants that protect cells from oxidative damage and have proliferative and anti-apoptotic activity. We investigated the effect of serum and phorbol ester treatment on expression of Prdx1 and Prdx6 in H2.35 cells, and the possible role of Sp1 on Prdx6 induction. Serum stimulation induced a 30% increase in Prdx1 mRNA and a three-fold increase in Prdx6 mRNA. We showed a similar effect of phorbol ester treatment, which led to a 30% increase in Prdx1 mRNA, and over a two-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…We have reported the induction of Prdx6 in H2.35 cells by serum, keratinocyte growth factor, and TNF-伪, 27,28 and we recently demonstrated that the proximal Prdx6 promoter, which includes several putative Sp1 binding sites and drives basal reporter expression in H2.35 cells, is inhibited by mithramycin A, a potent Sp1 inhibitor. 30 Since Sp1 is a redox-sensitive transcription factor that is deregulated in many cancer cells, 39 it may play a role in the up-regulation of Prdx6 in Hepa1-6 cells. Here, we have demonstrated that mithramycin A treatment differentially affects Prdx6 expression in our two cell lines, with no effect in H2.35 cells and a nearly 20% reduction in Hepa1-6 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported the induction of Prdx6 in H2.35 cells by serum, keratinocyte growth factor, and TNF-伪, 27,28 and we recently demonstrated that the proximal Prdx6 promoter, which includes several putative Sp1 binding sites and drives basal reporter expression in H2.35 cells, is inhibited by mithramycin A, a potent Sp1 inhibitor. 30 Since Sp1 is a redox-sensitive transcription factor that is deregulated in many cancer cells, 39 it may play a role in the up-regulation of Prdx6 in Hepa1-6 cells. Here, we have demonstrated that mithramycin A treatment differentially affects Prdx6 expression in our two cell lines, with no effect in H2.35 cells and a nearly 20% reduction in Hepa1-6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…30 To begin to investigate the differential regulation of Prdx6 between H2.35 and Hepa1-6 cells, we compared the effect of mithramycin A on Prdx6 expression in these two lines. As shown in Figure 3C, 4 h of mithramycin A treatment led to a nearly 20% reduction in Prdx6 expression in Hepa1-6 cells, while having no effect on Prdx6 expression in H2.35 cells.…”
Section: Differential Effect Of Mithramycin a On Prdx6 Expression In mentioning
confidence: 99%